BIMBINGAN LIFE SKILLS SEBAGAI UPAYA MENINGKATKAN KREATIVITAS PENYANDANG DISABILITAS INTELEKTUAL DI SENTRA TERPADU KARTINI TEMANGGUNG - Solchan Ghozali; Nurul Fadhilatun Nisa (Hijri, 2026)
This study aims to address the problems experienced by people with intellectual disabilities, who often experience discrimination in their environment, especially in the context of work. This problem has not yet received an adequate solution. As an effort to overcome this, government intervention in social rehabilitation is one of the important steps, which includes life skills guidance to support the independence of people with disabilities. Thus, the author presents two research questions formulated as follows: 1. What form of life skills guidance is given to people with intellectual disabilities at the Kartini Temanggung Integrated Center? 2. What efforts are made in life skills guidance to encourage the creativity of intellectual disabilities at the Kartini Temanggung Integrated Center? This study uses a qualitative research methodology with a case study approach. The data collection techniques applied include interviews, observations, and documentation, with a focus on activities related to life skills guidance, mentors, and individuals with intellectual disabilities themselves. The data collected were then analyzed using an analysis model developed by Miles and Huberman, which includes three main components: data reduction, data presentation, and data verification. The research findings show that the implementation of life skill guidance for people with intellectual disabilities at the Kartini Temanggung Integrated Center covers various dimensions, including mental guidance, spiritual guidance, psychosocial guidance, cognitive guidance, self-development guidance, and skills training in the fields of sewing, washing, culinary arts, and handicrafts. Efforts to improve the creativity of individuals with intellectual disabilities are implemented through various strategies, including product creation, exploration, imaginative activities, experimental projects, language and music development.